Natural resource harvesting and disturbance in communal lands: assessing the roles of local ecological knowledge, dependency and market access - Steele, Melita Zoë (Rhodes University, Faculty of Science, Department of Environmental Science, 2008)
A great deal of research has demonstrated that Non-Timber Forest Products (NTFPs) play a crucial role in the livelihoods of the rural poor, and are particularly important to the most marginalised people throughout the developing world. However, these livelihood benefits are not without cost to the natural resource base that rural communities depend so heavily upon. The continued dependence on NTFPs as a major livelihood source must be contingent upon the minimisation of the level of disturbance created through this dependency. This study assesses the level of disturbance created through natural resource harvesting in eight study sites around South Africa, and applies a predictive conceptual model created by Shankaar et al. (2004b) to try and ascertain under what conditions the level of disturbance created through natural resource harvesting will be high. It assesses the three key factors that Shankaar et al. (2004b) identified (level of Local Ecological Knowledge (LEK), level of dependency and access to markets) in relation to the level of disturbance found at each of the study sites. It was found that there was a statistically significant relationship between the level of dependency and the level of disturbance, but there was no statistically significant relationship between either access to markets or the level of LEK and disturbance. Regulation of land use is a key issue, with weak local institutions in communal areas making effective resource management difficult. The significance of these findings is discussed, and priorities for future research are identified. This study adds to the body of knowledge related to NTFP harvesting and critically analyses the conflicts between the livelihood gains and the level of disturbance created through NTFP harvesting in an attempt to ascertain how livelihoods can be safeguarded. And in the longer-term, so that management strategies can be identified where resource extraction is not at the cost of undermining the very livelihoods that depend upon the natural resource base.
Keywords: Non-timber forest products -- South Africa; Natural resources -- South Africa; Rural poor -- South Africa; Rural development -- South Africa; Forests and forestry -- South Africa; Households -- Economic aspects -- South Africa; Natural resources, Communal -- South Africa; Commons -- South Africa; Forest ecology -- South Africa; Harvesting